PWE-119 Decreased Frequency Of Peripheral And Intestinal Nkg2a-positive T Cells In Ulcerative Colitis Patients. (9th June 2014) - Kobayashi, W; Katsurada, T; Tomaru, U; Sakamoto, N; Kasahara, M
Abstract : Introduction: The intestinal tract is home to a numerous immune cellular components that continuously encounter abundant exogenous stimuli, where remain in a state of controlled inflammation normally. Inflammatory bowel disease (IBD) is characterised by chronic and refractory intestinal inflammation complising ulcerative colitis (UC) and Crohn's disease (CD) in main. Inhibitory natural killer receptors (iNKRs) are expressed on NK cells, involved in NK-cell tolerance to self. There is increasing evidence that iNKRs like NKG2A expressed on T cells are importantly involved in the regulation of immune responses though no studies have addressed the potential role in the pathogenesis of IBD. We analysed the expression of NKG2A on T cells in dextran sulfate sodium (DSS)-induced colitis model mouse and IBD patients. Methods: Male BALB/c mice were administrated 5% DSS in distilled water for 7 days ad libitum for induction of experimental colitis. For controls, age-matched BALB/c mice were given distilled water. NKG2A+ T cells in peripheral blood mononuclear cells (PBMCs) and lamina propria mononuclear cells (LPMCs) were analysed by flow cytometry. For histological analysis of DSS-induced colitis mice, hematoxylin and eosin (HandE) staining and immunohistochemistry were performed. For blocking experiments using antibody (Ab), mice were intraperitoneally injected with 300 µg of anti-NKG2A monoclonal Ab or control IgG after oral administration of 5% DSS. PBMCs samples from 23 healthy controls, 20 UC and 16 CD patients were analysed by flow cytometry. Tissue sections from 7 controls, 6 UC and 5 CD patients were subjected to histological analysis. Data were evaluated using the Student's t -test or the Mann-Whitney U-test. Results: In the active phase of DSS-induced colitis mouse, the frequency of NKG2A+ T cells was significantly decreased in the peripheral blood and increased in the intestine, suggesting the mobilisation of this T cell subset to the sites of inflammation. Administration of anti-NKG2A Ab increased the number of inflammatory foci in DSS-induced colitis, suggesting the involvement of NKG2A+ T cells in this colitis model. In UC patients, the frequency of NKG2A+ T cells in PBMCs was significantly decreased, compared with CD patients and healthy controls, regardless of clinical conditions. Notably, in sharp contrast to the DSS-induced colitis mouse, the frequency of NKG2A+ cells in LPMCs was also decreased in UC patients. Conclusion: These results suggest that inadequate local infiltration of NKG2A+ T cells may be involved in the pathogenesis of UC. Our study demonstrates the frequency of NKG2A+ T cells is decreased in both PBMCs and LPMCs in UC patients, implicating this T cell subset as a potential therapeutic target for UC. Disclosure of Interest: None Declared.